Amantadine inhibits platelet-activating factor induced clathrin-mediated endocytosis in human neutrophils - Eckels, Phillip C. (American Physiological Society, 2009)
Receptor signaling is integral for adhesion, emigration, phagocytosis, and reactive oxygen species production in polymorphonuclear neutrophils (PMNs). Priming is an important part of PMN emigration, but it can also lead to PMN-mediated organ injury in the host. Platelet-activating factor (PAF) primes PMNs through activation of a specific G protein-coupled receptor. We hypothesize that PAF priming of PMNs requires clathrin-mediated endocytosis (CME) of the PAF receptor (PAFr), and, therefore, amantadine, known to inhibit CME, significantly antagonizes PAF signaling. PMNs were isolated by standard techniques to >98% purity and tested for viability. Amantadine (1 mM) significantly inhibited the PAF-mediated changes in the cellular distribution of clathrin and the physical colocalization [fluorescence resonance energy transfer positive (FRET(+))] of early endosome antigen-1 and Rab5a, known components of CME and similar to hypertonic saline, a known inhibitor of CME. Furthermore, amantadine had no effect on the PAF-induced cytosolic calcium flux; however, phosphorylation of p38 MAPK was significantly decreased. Amantadine inhibited PAF-mediated changes in PMN physiology, including priming of the NADPH oxidase and shape change with lesser inhibition of increases in CD11b surface expression and elastase release. Furthermore, rimantadine, an amantadine analog, was a more potent inhibitor of PAF priming of the N-formyl-methionyl-leucyl-phenylalanine-activated oxidase. PAF priming of PMNs requires clathrin-mediated endocytosis that is inhibited when PMNs are pretreated with either amantadine or rimantadine. Thus, amantadine and rimantadine have the potential to ameliorate PMN-mediated tissue damage in humans.